Characterization of plantar pressures in visually impaired individuals: A pilot study - Abu-Faraj, Ziad O.; Faraj, Yasmeen T.; Mohtar, Khalil H.; Rammal, Maryam M. (2013 6th International IEEE/EMBS Conference on Neural Engineering (NER), 2013)
The ambulatory forces exerted underneath the plantar surface of the foot of visually-impaired individuals have not been fully studied. Accordingly, the objective of this pilot study is to characterize the plantar pressures in the said individuals using a pedar-x (novel gmbh, Munich, Germany) in-shoe dynamic plantar pressure measurement system. A foot mask, dividing each of the insoles into seven plantar loading regions, is employed in this study. This paper reports preliminary results obtained from two physically abled, normal-sighted control individuals and three visually-impaired subjects. The study metrics included: mean peak plantar pressure, foot-to-ground contact duration, insole loading area, pressure-time integral, and the position, displacement, and instantaneous velocity of the center of pressure. The results reveal that there is noticeable variability in the peak plantar pressure distribution among the test subjects. Such results reflect non-homogeneity in foot biomechanics of visually-impaired individuals that is believed to be due to their cautious walking strategy. The visually-impaired subjects exhibited prolonged foot-to-ground contact durations and a naturally improvised COP trajectory. A generalized conclusion can be attained upon expanding the current study to include a larger sample population of both normal control and visually impaired.